Crystallization and X‐ray diffraction analysis of native and selenomethionine‐substituted PhyH‐DI from Bacillus sp. HJB17. Issue 11 (2nd November 2017) - Lu, Fang; Zhang, Bei; Liu, Yong; Song, Ying; Guo, Gangxing; Feng, Duo; Huang, Huoqing; Yang, Peilong; Gao, Wei; Guo, Sujuan; Yao, Bin
Abstract : PhyH‐DI, a β‐propeller phytase from Bacillus sp. HJB17 that interacts with PhyH‐DII and other typical β‐propeller phytases, can increase the efficiency of phytases in hydrolyzing phytate. Native and selenomethionine‐substituted PhyH‐DI were expressed, purified and crystallized. Abstract : Phytases are phosphatases that hydrolyze phytates to less phosphorylated myo ‐inositol derivatives and inorganic phosphate. β‐Propeller phytases, which are very diverse phytases with improved thermostability that are active at neutral and alkaline pH and have absolute substrate specificity, are ideal substitutes for other commercial phytases. PhyH‐DI, a β‐propeller phytase from Bacillus sp. HJB17, was found to act synergistically with other single‐domain phytases and can increase their efficiency in the hydrolysis of phytate. Crystals of native and selenomethionine‐substituted PhyH‐DI were obtained using the vapour‐diffusion method in a condition consisting of 0.2  M sodium chloride, 0.1  M Tris pH 8.5, 25%( w / v ) PEG 3350 at 289 K. X‐ray diffraction data were collected to 3.00 and 2.70 Å resolution, respectively, at 100 K. Native PhyH‐DI crystals belonged to space group C 121, with unit‐cell parameters a  = 156.84, b  = 45.54, c  = 97.64 Å, α = 90.00, β = 125.86, γ = 90.00°. The asymmetric unit contained two molecules of PhyH‐DI, with a corresponding Matthews coefficient of 2.17 Å 3  Da −1 and a solvent content of 43.26%. Crystals of selenomethionine‐substituted PhyH‐DI belonged to space group C 2221, with unit‐cell parameters a  = 94.71, b = 97.03, c = 69.16 Å, α = β = γ = 90.00°. The asymmetric unit contained one molecule of the protein, with a corresponding Matthews coefficient of 2.44 Å 3  Da −1 and a solvent content of 49.64%. Initial phases for PhyH‐DI were obtained from SeMet SAD data sets. These data will be useful for further studies of the structure–function relationship of PhyH‐DI.